Dual IGF1R/IR inhibitors in combination with GD2-CAR T-cells display a potent anti-tumor activity in diffuse midline glioma H3K27M-mutant. Issue 7 (29th December 2021) - de Billy, Emmanuel; Pellegrino, Marsha; Orlando, Domenico; Pericoli, Giulia; Ferretti, Roberta; Businaro, Pietro; Ajmone-Cat, Maria Antonietta; Rossi, Sabrina; Petrilli, Lucia Lisa; Maestro, Nicola; Diomedi-Camassei, Francesca; Pezzullo, Marco; et al.
Abstract: Background: Diffuse midline gliomas (DMG) H3K27M-mutant, including diffuse intrinsic pontine glioma (DIPG), are pediatric brain tumors associated with grim prognosis. Although GD2-CAR T-cells demonstrated significant anti-tumor activity against DMG H3K27M-mutant in vivo, a multimodal approach may be needed to more effectively treat patients. We investigated GD2 expression in DMG/DIPG and other pediatric high-grade gliomas (pHGG) and sought to identify chemical compounds that would enhance GD2-CAR T-cell anti-tumor efficacy. Methods: Immunohistochemistry in tumor tissue samples and immunofluorescence in primary patient-derived cell lines were performed to study GD2 expression. We developed a high-throughput cell-based assay to screen 42 kinase inhibitors in combination with GD2-CAR T-cells. Cell viability, western blots, flow-cytometry, real time PCR experiments, DIPG 3D culture models, and orthotopic xenograft model were applied to investigate the effect of selected compounds on DIPG cell death and CAR T-cell function. Results: GD2 was heterogeneously, but widely, expressed in the tissue tested, while its expression was homogeneous and restricted to DMG/DIPG H3K27M-mutant cell lines. We identified dual IGF1R/IR antagonists, BMS-754807 and linsitinib, able to inhibit tumor cell viability at concentrations that do not affect CAR T-cells. Linsitinib, but not BMS-754807, decreases activation/exhaustion of GD2-CAR T-cells and increases their central memory profile. The enhanced anti-tumor activity of linsitinib/GD2-CAR T-cell combination was confirmed in DIPG models in vitro, ex vivo, and in vivo. Conclusion: Our study supports the development of IGF1R/IR inhibitors to be used in combination with GD2-CAR T-cells for treating patients affected by DMG/DIPG and, potentially, by pHGG.